Archaeological Research of the Late Scythian Site of Frontovoye 2 in 2018 - Sharov, Oleg (Hyperboreus, 2019)
A survey of the excavations on the late Scythian site of Frontovoye 2 conducted by the Crimean Rescue Archaeological Expedition (CRAE) of the Institute of Archaeology of the Russian Academy of Sciences in 2018.